The Effectiveness of Papaya Leaves and Chili Pepper (Capsium fructescens) as Bioinsecticide for White Oyster Mushroom (Pleuroutus ostreatus) Cultivation - Margaretta , Margaretta Christita; Suryawan, Ady Suryawan (Forestry Department, University of Muhammadiyah Makassar, 2018)
This study purposes to compare the effectiveness of bio-insecticides made from papaya leaf extract, and chilli pepper in several different doses to reduce pest attack on white oyster mushroom (Pleurotus ostreatus). Experiments conducted on oyster mushrooms that are fruitful with 3 formula are formula 1 (papaya and water), Formula 2 (papaya leaves, chili pepper, and water), and the formula 3 (chili pepper and water). Parameters observed were the fallen fruit, harvest weight, fruit diameter, the number of dead pests. The results concluded that the formula has a significant effect on all parameters. Formula 2 has the highest level of effectiveness of insecticides can reduce the fallen fruit to 84 %, have twice yields and 1.3 times bigger diameter than control crop yields. Formula 2 has the composition of papaya leaf extract and chili pepper (1:1:2)